SLIPS OF THE EARS: STUDY ON VOWEL PERCEPTION IN INDONESIAN LEARNERS OF ENGLISH - Arum Perwitasari (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2013)
Slips of the ears leads to speakers’ misperception and misunderstanding. It hints at communication failure between the speaker and the listener. Yet, linguists have not conducted full investigation on this matter. This research is designed to identify vowel sounds misperceived by Indonesian learners of English. Moreover, it examines the bearing of context and the causes of slips of the ears among those learners. A Questionaire and listening tests were used for data collection. The questionaire was employed to explore the respondents’ personal information. Analysis of the data commence with the identification of vowel sounds that are misperceived by the respondents. It guides the research to find the mean and percentage of listening test with and without context. The research provides strong evidence that context has a positive influence on learners’ comprehension of words. Accordingly, the research comes to the point that the causes of slips of the ear are interlingual and extralingual factors.